Gamma-ray irradiation alters the morphology, anatomy and agronomic characters of the groundnut (Arachis hypogaea) bison cultivar in M1 generation - NILAHAYATI NILAHAYATI; RD. SELVY HANDAYANI; NAZIMAH NAZIMAH; NENI NENI; DIMAS SAPUTRA (Society for Indonesian Biodiversity, 2024)
Abstract. Nilahayati, Handayani RS, Nazimah, Neni, Saputra D. 2024. Gamma-ray irradiation alters the morphology, anatomy and agronomic characters of the groundnut (Arachis hypogaea L.) bison cultivar in M1 generation. Biodiversitas 25: 4179-4189. Groundnut is the world's most important agricultural commodity, serving as a major source of protein and vegetable oil. Enhancing the genetic diversity of groundnuts is essential for improving yield, early maturity and environmental resistance such as drought tolerance. This study aims to determine the effect of gamma irradiation on the morphological and agronomic diversity of bison groundnut cultivar in the M1 generation. Gamma irradiation was carried out at the Radiation Process Technology Research Center, National Research and Innovation Agency of Indonesia, Jakarta. This research was designed using a single-factor Randomized Complete Block Design. The dose of gamma irradiation was 0 Gray (Gy), 100 Gy, 200 Gy, and 300 Gy, with three replications. Consequently, there were a total of 12 experimental units. We generated 600 groundnut plants in total. The observed variables included morphological diversity such as variation in leaf, stem, seed color and seed shape. The agronomic variability was recorded to the seed growth percentage, plant height, number of branches, flowering age, harvesting age, number of pods, number of empty pods, dry pod weight per plant, dry seed weight per plant, 100 seed weight per plot, dry seed weight per plot, length, width, and number of leaf stomata. The results showed that gamma irradiation treatment induced morphological and agronomic changes in the bison groundnut cultivar. Morphological changes included alterations in leaf color, pod shape, and seed coat color. Higher doses of gamma irradiation can negatively impact certain agronomic traits such as plant height and yield, beginning at 200 Gy, but at 100 Gy all parameters slightly increased. Higher dose of gamma irradiation also delayed the flowering and harvesting time. Further studies are also needed to evaluate the heritability of these traits in the M2 generation to ensure the stability of desirable traits.